Singing the Individual: Name Tunes in Oyda and Yopno - Amha, Azeb; Slotta, James; Sarvasy, Hannah S. (Frontiers in Psychology, 2021)
Music beats spoken language in identifying individuals uniquely in two disparate communities. In addition to their given names, which conform to the conventions of their languages, speakers of the Oyda (Omotic; SW Ethiopia) and Yopno (Finisterre-Huon Papuan; NE Papua New Guinea) languages have ‘name tunes,’ short 1-4-second melodies that can be sung or whistled to hail or to identify for other purposes. Linguistic given names, for both communities, are often non unique: people may be named after ancestors or contemporaries, or bear given names common to multiple individuals. But for both communities, name tunes are generally non-compositional and unique to individuals. This means that each new generation is likely to bring thousands of new name tunes into existence. In both communities, name tunes are produced in a range of contexts, from quotidian summoning and mid-range communication, to ceremonial occasions. In their use of melodies to directly represent individual people, the Oyda and Yopno name tune systems differ from surrogate speech systems elsewhere that either: a) mimic linguistic forms, or b) use music to represent a relatively small set of messages. Also, unlike some other musical surrogate speech traditions, the Oyda and Yopno name tune systems continue to be used productively, despite societal changes that have led to declining use in some domains.